Global Goal on Adaptation - COP29 Negotiation Update - Njuguna, Lucy; Nepal, Santosh; Mukherji, Aditi (2024)
The 2015 Paris Agreement’s Article 7 set a global goal on adaptation to improve adaptive capacity, resilience, and reduce vulnerability to climate change, supporting sustainable development. To achieve this, the Glasgow-Sharm el-Sheikh work program was launched at COP 26 (2021) to guide efforts under the Subsidiary Bodies (SBSTA and SBI).